TREN DAN DINAMIKA PENELITIAN AKUNTANSI BERKELANJUTAN: TINJAUAN BIBLIOMETRIK TERHADAP PUBLIKASI INTERNASIONAL TERBITAN TAHUN 2010-2025 - Judijanto, Loso; Puspa, Eka Septariana; Putra Hernat, Okevanrianus (Gapenas Publisher, 2025)
This study aims to map the trends and dynamics of sustainable accounting research at the global level by using a bibliometric approach to international publications during the period 2010 to 2025. By analyzing data from the Scopus database and visualizing it through the VOSviewer software, the study identified the development of the number of publications, collaborations between authors and institutions, as well as the dominant themes in the literature. The results of the analysis show that the topics of digital accounting, blockchain, artificial intelligence, and ESG reporting have increased significantly in the last five years, illustrating the shift in research focus towards digitalization and sustainability in accounting practices. In addition, global collaborations involving countries such as the United States, Saudi Arabia, and Jordan further strengthen interdisciplinary knowledge ecosystems. The study provides theoretical contributions through mapping the knowledge structure in the field of sustainable accounting, as well as practical implications for academics, practitioners, and policymakers in responding to the challenges of digital transformation and the sustainability agenda. These findings also open up opportunities for further research that is conceptually and contextually in-depth.